What determines private school choice? A comparison between the UK and Australia - Lorraine Dearden; Chris Ryan; Luke Sibieta (Institute for Fiscal Studies (IFS), 2010)
This paper compares patterns of private school attendance in the UK and Australia. About 6.5% of school children in the UK attend a private school, while 33% do so in Australia. We use comparable household panel data from the two countries to model attendance at a private school at age 15 or 16 as a function of household income and other child and parental characteristics. As one might expect, we observe a strong effect of household income on private school attendance. The addition of other household characteristics reduces this income elasticity, and reveals a strong degree of intergenerational transmission in both countries, with children being 8 percentage points more likely to attend a private school if one of their parents attended one in the UK, and anywhere up to 20 percentage points more likely in Australia. The analysis also reveals significant effects of parental education level, political preferences, religious background and the number of siblings on private school attendance.
Keywords: 330; Privatschule; Schulauswahl; Haushaltseinkommen; Sozialer Status; Vergleich; Großbritannien; Australien